THE EFFECT OF GOOD CORPORATE GOVERNANCE MECHANISM, FINANCIAL DISTRESS ON EARNING MANAGEMENT BEHAVIOR : EMPIRICAL STUDY IN PROPERTY AND INFRASTRUCTURE INDUSTRY IN INDONESIAN STOCK EXCHANGES - Ahmad Fauzan Fathoni; Haryetti '; Errin Yani Wijaya; Muchsin ' (Jurnal Ekonomi, 2014)
The goal of this reseach is to examine the effect of Good Corporate GovernanceMechanism, Financial Distress on Earning Management Behaviour withFinancial Distress as inteveing variabel. We use some proxies to measure GoodCorporate Governance mechanism, namely: Manajerial Ownership, InstitusionalOwnership, Propotion of Independen Commissioners, and Audit Committee. Inaddition, Altman Z-scores is used as financial distress proxy.We use panel data that uses cross section and time series data from Property andInfrastructure Industry in Indonesian Stock Exhange during 2009-2011 periods.Ordinary Least Squared is used to analyze the data.The result shows that Managerial Ownership, Institutional Ownership, Propotionof Independen Commisioners, and the Number of Audit Committee have negativeeffect toward earning management behavior. On the other hand, only the numberof Audit committee and Proportion of Independen Commisioners variables thathave significant effect. Moreover, Financial Distress has positive effect onearning management but not significance. In addition to those results, themoderation effect shows that the firms that financially distressed tend to attemptto manipulate their earning even they have done Good Corporate Governancemechanism.Keywords : Good Corporate Governance Mechanism, Financial Distress,Earning Management Behavior